The Switching Intention of Gen Z to Bring Tumblers: The Pro-Environmental Predictors - Archie, Ananda; Madepo, Mahardika Agung; Ramadaniar, Nur (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
Pro-environmental behavior affects many aspects, including the coffee industry with eco-friendly packaging such as tumblers. This under investigated trend involves the Generation Z for their environmental concern. This research examines the role of attitude in mediating the influence of environmental knowledge, environmental concern, and social influence on the intention to switch to bringing a tumbler to a coffee shop. This research uses quantitative approaches with 300 data were collected through an online questionnaire. Employing Structural Equation Model (SEM) with SmartPLS application, the results showed that environmental knowledge is not significant to attitude, environmental concern is not significant to switching intention, and attitude does not mediate the effect of environmental knowledge on switching intention. However, other hypothesized relationships in the model were statistically supported. These findings encourage coffee shops to take advantage of the changing behavior of Generation Z by developing strategies that target environmental concerns.